2020
DOI: 10.1101/2020.05.07.20093286
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-ancestry omic Mendelian randomization revealing putative drug targets of COVID-19 severity

Abstract: Drug target prioritization for new targets and drug repurposing of existing drugs for COVID-19 treatment are urgently needed for the current pandemic. COVID-19 drugs targeting human proteins will potentially result in less drug resistance but could also exhibit unintended effects on other complex diseases. Here we pooled 353 candidate drug targets of COVID-19 from clinical trial registries and the literature and estimated their putative causal effects in 11 SARS-CoV-2 related tissues on 622 complex human disea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 112 publications
0
9
0
Order By: Relevance
“… 58 In a recent multiomics study, dihydroorotate dehydrogenase was identified as a possible target for SARS-CoV-2 infection. 59 In addition, leflunomide has been shown to inhibit SARS-CoV-2 activity. 60 Diltiazem hydrochloride is a calcium channel blocker that helps to increase blood flow and variably decrease the heart rate via strong depression of the A-V node.…”
Section: Resultsmentioning
confidence: 99%
“… 58 In a recent multiomics study, dihydroorotate dehydrogenase was identified as a possible target for SARS-CoV-2 infection. 59 In addition, leflunomide has been shown to inhibit SARS-CoV-2 activity. 60 Diltiazem hydrochloride is a calcium channel blocker that helps to increase blood flow and variably decrease the heart rate via strong depression of the A-V node.…”
Section: Resultsmentioning
confidence: 99%
“… 37 , 38 Thus, comprehensive assessment of the causal effects of COVID-19 drug targets on disease phenotypes will provide key information regarding their safety issue ( Figure 3 ). 39 …”
Section: Genetic Insights Into Covid-19mentioning
confidence: 99%
“…The de novo pyrimidine biosynthesis pathway is also critical for the excessive production of a subset of inflammatory cytokines (including interferon-gamma, monocyte chemoattractant protein-1 [MCP-1], IL-5, and IL-6) in both cultured cells and animal models of viral infection (Cheung et al, 2017;Xiong et al, 2020a). Consistent with DHODH being mechanistically central to the progression of COVID-19, a recent multi-omics study of drug targets for viral infections prioritized DHODH inhibition as one of the top three mechanisms to consider for SARS-CoV-2 treatment (Zheng et al, 2020).…”
Section: Introductionmentioning
confidence: 99%